Razmerje med človeško in umetno inteligenco v luči Habermasove teorije - Gregorčič, Rok (Bogoslovni vestnik, 2024)
The aim of this article is to investigate the relation between human and artificial intelligence in light of the theory of communicative rationality. In the first part, Habermas's theoretical starting points are presented. Primarily, the transition from a monological to a communicative form of rationality is emphasized. In the next step, the focal point is moved toward the distinction between inductive and deductive systems of AI. In relation to this, a historical examination of the first and second wave of AI research in the previous century is also presented. A thesis that interprets the transition from symbolic AI to connectionism in correlation to Habermas's transition from monological to communicative rationality is thoroughly analyzed. Towards the end of the article, another way of applying Habermas's theory to the relation between human and artificial intelligence is presented. Deriving from Habermas's criticism of liberal eugenics, a well-argumented position emerges that could help us distinguish between humans and AI in the long run.
Keywords: artificial intelligence; communicative rationality; connectionism; genetic manipulation; genetska manipulacija; Habermas, Jürgen; komunikativna racionalnost; konekcionizem; simbolizem; symbolism; umetna inteligenca